2003
DOI: 10.1002/ajmg.b.20019
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism analysis of HOPA: A candidate gene for schizophrenia

Abstract: HOPA is a 25 kb Xq13 gene that codes for a member of the thyroid receptor co-activator protein (TRAP) family of nuclear receptor co-activators. In our prior research, polymorphisms in the opposite paired (Opa) domain of HOPA have been associated with a syndrome of aberrant behavior, most prominently psychosis, and hypothyroidism. These Opa domain polymorphisms are intriguing because subsequent research has demonstrated that changes in the Opa domain of the C. elegans orthologue of HOPA results in altered neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…Fourth, it should be noted that the HOPA 12bp polymorphism itself is in linkage disequilibrium with a substantial haplotype on Xq13. Therefore, even if the current analyses are correct, it is possible that the HOPA 12bp polymorphism may not be responsible for some or all the effects associated with this haplotype, although the results of Sandhu et al (2003) make this possibility less likely. Fifth and finally, secondary to the low number of observations of the HOPA 12bp allele, the As an overlapping control group was used in the DeLisi and Philibert studies, the result of these two studies were pooled for this analysis with the resulting joint odds ratio being reported on the line for the Philibert et al study.…”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…Fourth, it should be noted that the HOPA 12bp polymorphism itself is in linkage disequilibrium with a substantial haplotype on Xq13. Therefore, even if the current analyses are correct, it is possible that the HOPA 12bp polymorphism may not be responsible for some or all the effects associated with this haplotype, although the results of Sandhu et al (2003) make this possibility less likely. Fifth and finally, secondary to the low number of observations of the HOPA 12bp allele, the As an overlapping control group was used in the DeLisi and Philibert studies, the result of these two studies were pooled for this analysis with the resulting joint odds ratio being reported on the line for the Philibert et al study.…”
Section: Resultsmentioning
confidence: 50%
“…Two studies (Kirov et al, 2003;Sandhu et al, 2003) examined the relationship of the HOPA 12bp allele by transmission disequilibrium testing (TDT) using trios informative for an X-chromosome loci (i.e. using only the mothers of probands as fathers of probands only have one X-chromosome).…”
Section: Transmission Disequilibrium Testingmentioning
confidence: 99%
“…It has been shown that med12 gene is essential for early development in mouse and is involved in the transcriptional regulation of many signaling pathways (Philibert and Madan, 2007, Rocha et al, 2010). MED12 has been shown to be implicated in a number of neurological disorders (Xu et al, 2011, Philibert and Madan, 2007, Sandhu et al, 2003, Graham and Schwartz, 2013, Risheg et al, 2007, Schwartz et al, 2007, Ding et al, 2008) as well as human cancers (Schiano et al, 2014, Turunen et al, 2014, Huang et al, Shalem et al, 2014, Wang et al, 2015). Particularly, MED12 was linked to drug resistance in multiple cancer types including breast, colon, lung cancers and melanoma (Wang et al, 2015, Shalem et al, 2014, Huang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Also codes proteins critical in the regulation of transcription via the Wnt and receptor tyrosine kinase pathways, both of which are involved in cell differentiation and growth [70].…”
Section: Hopa Xq13mentioning
confidence: 99%